DAMPAK PENGEMBANGAN AGROWISATA KOPI TERHADAP SOSIAL EKONOMI PETANI DI DESA COLOL KECAMATAN LAMBA LEDA TIMUR KABUPATEN MANGGARAI TIMUR - Nalo, Katarina; Adar, Damianus; Siubelan, Yacobus C.W. (Undana Press, 2023)
This research was conducted in Colol Village, East Lamba Leda District, East Manggarai Regency in February 2023. This study aims to determine: (1) the activities carried out by coffee agrotourism farmers in Colol Village (2) the impact of developing coffee agrotourism on the socio-economic conditions of farmers (3) Differences in income of coffee agro-farmer farmers before and after Colol Coffee Agro-tourism was established (4) contribution of coffee farming income to coffee farmer household income. The analytical tool used is the Paired Sample T-test and Revenue Contribution analysis. The results showed that (1) the activities carried out by Colol Coffee Agrotourism farmers in tourist attraction areas such as: land clearing, promoting and selling coffee, making agrotourism facilities, a guide caffee shop and home stay (2) the impact of Colol Coffee Agrotourism development brought socio-economic changes to the people in Colol Village such as: Increasing job opportunities and training people to be more creative and innovative (3) the income of farmers after the inauguration of agro-tourism is higher than the income of farmers before the inauguration of agro-tourism, which is shown by the results of the Paired Sample T-test which has a value of 0.015 (<0.05) (4) The amount of contribution from coffee farming to the total farmer household income that is equal to 79,55%.